Ending Fault in Accident Compensation: Issues and Lessons from Medical Misadventure - Easton, Brian (Victoria University of Wellington Law Review, 2004)
This paper suggests that emphasising prevention and rehabilitation are the key directions that the ACC system should move in the future. Compensation should be phased out in favour of rehabilitation as the primary means of remediation. Additionally the author recommends removing inequity in the system by phasing out accidents as the basis for entitlement and replacing it with an entitlement regime based on injury outcomes. This discussion is located within the context of the treatment of medical misadventure under the ACC system.